2021
DOI: 10.1021/acsaem.1c01536
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Efficiency of GaSb Photovoltaic Cell Using Thin-Film Multiscale Haze and Radiative Cooling

Abstract: In this work, a multiscale thin-film membrane of self-aggregated anodized aluminum oxide (AAO) nanowire structure was developed to enhance the efficiency of GaSb photovoltaic (PV) cell using both optical haze and passive radiative-cooling effects in a broad region of the solar spectrum. We controlled, (1) the optical properties of thin-film AAO and (2) the plasmonic-induced perfect absorption/emission by changing packing densities and lengths of AAO nanowires during the anodization and wet etching processes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In fact, with the inherent photonic band gap (PBG) behaviors in the field of passive cooling and thermal insulation, CPCs have received extensive attention. To date, researchers have already made some efforts and revealed that highly ordered structure could efficiently reflect heat back to the surroundings to achieve passive cooling and thermal insulation. Here, from the implementation point of view, we directly assembled the colloidal particles onto the substrate to achieve thermal insulation. Figure shows the average temperature difference between the CPCs films and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, with the inherent photonic band gap (PBG) behaviors in the field of passive cooling and thermal insulation, CPCs have received extensive attention. To date, researchers have already made some efforts and revealed that highly ordered structure could efficiently reflect heat back to the surroundings to achieve passive cooling and thermal insulation. Here, from the implementation point of view, we directly assembled the colloidal particles onto the substrate to achieve thermal insulation. Figure shows the average temperature difference between the CPCs films and the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…17 Gupta et al demonstrated that the temperature of a bare GaSb cell reduces by ∼26 K after attaching a thin membrane of self-aggregated, anodized aluminum-oxide-based, 30 μm-length nanowires. 18 Cho et al fabricated 7 μm-deep, oxide-based hollow-cavity films that lower the undoped-Si wafer temperature by ∼10 K and boost solar absorptivity. 19 The abovementioned studies demonstrate thin radiative coolers that provide substantial thermal improvements, but their overall impact on sensitive-material-based USCs is questionable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Perrakis et al demonstrated that by designing a thin and scalable radiative cooler based on superimposed in-plane nano- and microscaled (∼2 μm) periodic patterns on glass, the temperature of a doped silicon cell reduces by up to ∼5.8 K, despite the remarkably augmented solar absorption within silicon’s spectral pass-band edges . Gupta et al demonstrated that the temperature of a bare GaSb cell reduces by ∼26 K after attaching a thin membrane of self-aggregated, anodized aluminum-oxide-based, 30 μm-length nanowires . Cho et al.…”
Section: Introductionmentioning
confidence: 99%
“…Highly ordered anodic porous alumina, which has a nanohoneycomb structure composed of uniform-sized cylindrical pores, has attracted much attention as a key material for fabricating various functional devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] If highly ordered anodic porous alumna can be directly formed on substrates such as Si wafers and indium tin oxide (ITO) -coated glass, it is expected to have various applications in, for example, magnetic recording media, sensors, and templates for preparing one-dimensional nanostructures on the substrates. It has been reported that anodic porous alumina is formed on substrates by forming an Al film by sputtering or thermal evaporation and subsequent anodization in an acidic solution.…”
mentioning
confidence: 99%